Analisis Sinematografi Menggunakan Teknik Camera Angle dan Type of Shot Pada Sosial Media Mempengaruhi Minat Penonton Terhadap Ekowisata Silowo - Herwina, Nevlin Cresentia; Daniar, Aninditya; Wardani, Nuril Kusuma (Peneliti.net, 2024)
This analysis aims to discuss the cinematographic elements in the Silowo Ecotourism video reels,Instagram @kabupacepatban using camera movement techniques and types of shots. SilowoEcotourism Video Reels is a program implemented by Diskominfo-SP Tuban. These video reels presentinformation about tourism in Tuban as a medium for delivering information and digital marketing. Thevideo reels are packaged using cinematographic elements. This research uses a qualitative descriptiveresearch method. From the analysis, it is revealed that the cinematographic elements that are the mainpoints in enhancing the aesthetics of the video are camera angle and type of shot. With the cameraangle technique and type of shot in the Silowo Ecotourism video, the image of the tourist spot can bebuilt so that the audience's interest in visiting the place is higher